Construction strategies for 3D printed cardiac tissue repair materials and their application potential - Mingru Kong; Zhen Wu; Zeliang Zheng; Binrui Zhang; Yuting Zeng; Hao Deng; Dongyi Feng; Wenjun Zhang; Congru Li; Xiaodong Fu; Leyu Wang (Interdisciplinary Medicine)
Abstract As a major cause of death worldwide, heart disease has significant limitations in traditional treatments. However, 3D printing technology, with its personalized, precise, and multifunctional features, provides a new idea for developing cardiac tissue repair materials. This review analyzes the three core advantages of 3D printing technology in cardiac repair materials: the realization of personalized medicine, the intelligent construction of complex tissue structures, and the optimization of the functions of multi‐material combinations. Combined with specific research cases, this review reveals the progress of 3D printing in heart valve replacement, heart patches, vascular stent manufacturing, and composite material development, especially the potential of carbon‐based conductive materials, biomass‐based materials, and bio‐based materials in cardiac tissue repair. In addition, this review discusses the innovative applications of advanced 3D printing technologies in the design of prosthetic materials, including coaxial printing, microfluidic extrusion printing, stereospecific rapid prototyping, and two‐photon printing. Finally, this review summarizes the significant advantages of 3D printing technology in cardiac tissue repair and proposes future research directions. It emphasizes the importance of combining 3D printing technology with the study of cardiac tissue engineering to further improve the performance and repair effectiveness of cardiac repair materials. Meanwhile, the potentials of single‐cell technology, spatial genomics, and protein prediction technology in optimizing the biocompatibility and functionality of repair cardiac repair materials are envisioned to provide scientific support for more efficient cardiac tissue repair through precise regulation of cell behavior, remodeling of the tissue microenvironment, and the development of personalized materials.